2015
DOI: 10.1097/ans.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Survivor Guilt

Abstract: Survivor guilt, a concept associated with the interpersonal process of "surviving" harm while others do not, increasingly appears in nursing, medicine, and psychology literature. Paradoxically, the phenomenon is rarely defined and often poorly described. Combining Rodger's evolutionary concept analysis with a comprehensive literature review, we explain the attributes, antecedents, consequences, related concepts, and surrogate terms of survivor guilt. A new definition emerged from the evolving use of the concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Furthermore, Williams et al (2000) mentioned that survivor guilt was a common experience in their study of ten non-carriers. A recent concept analysis of survivor guilt has divided the consequences into four main reactions: altered identity, altered relationships, mental health and physical symptoms and resolution (Hutson et al 2015). Among the participants in our study, we could identify all reactions except resolution (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, Williams et al (2000) mentioned that survivor guilt was a common experience in their study of ten non-carriers. A recent concept analysis of survivor guilt has divided the consequences into four main reactions: altered identity, altered relationships, mental health and physical symptoms and resolution (Hutson et al 2015). Among the participants in our study, we could identify all reactions except resolution (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…An expression of altered relationships was stated by a participant who avoided contact with the rest of the family due to feelings of guilt. On the other hand, Hutson et al (2015) also showed that a person can successfully recover from survivor guilt by changing behaviour in a positive way (an example of altered identity). In the present study, one of the participants started to take a greater responsibility of her affected sibling's care and also exhibited positive changes in personal health behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 In 1576, Ludovico Castelvetro produced a detailed taxonomy of ways to bring the complexity of all that cannot be staged before the minds of the audience: this included the 'web of incidents' leading up to the present; actions taking place at some distance from the scene, and actions made known by supernatural means (dreams or apparitions). 38 Shakespeare's rewritings of earlier plays show his interest in these new techniques: he frequently rewrote staged actions as what I am calling 'unscenes'-that is, hints, recollections, dreams, descriptions of events elsewhere. And while Anglophone critics have assumed 'reporting' to be inferior to 'staging', this assumption does not bear close scrutiny.…”
mentioning
confidence: 99%